PENGARUH KOMPOSISI CAMPURAN SERPIB KAYU DAN KONSENTRASI LARUTAN PEMASAK NaOH TERHADAP SIFAT PAPAN SERAT BEKERAPATAN SEDANG - Ridwan Achmad Pasaribu (Pusat Penelitian dan Pengembangan Hasil Hutan, 1994)
A research has been done to mix four plantation wood species, i.e., Acacia mangium (mangium ), Paraserianthes falcataria (sengon), Eucalyptus urophylla (ampupu) and E. deglupta (leda) for wood pulp. Pulping process is semichemical open caustic soda. Pulp that have been processed then formed. into-MDF with wet process. physical and mechanical lests are done for density, moisture content, water absorption, thickness and volume swelling, tensile strength, modulus of elasticity :Range of pulp yield produced in the experiment was 67-82%. The mixed wood composition of 25% mangiuin, 28% sengon, 24% ampupu and 23% leda, processed wilh 35 g/l NaOH produced pulp yield in accordance with FAO standard, like wise, mixed wood camposilion of 32 % mangiun, 37% sengon and 31 % ampupu cooked with 35 and 40 g/l NaOH Physical and mechanical properties for five mixed wood compositions done in the experiment meet FAO standard if processed with 35 g/l NaOH, except for tensile strerigth. The resulis showed that wood chips composition, cooking liquor coecentration of them caused a significant effecl on tensile strength, modulus of rupture and modulus of elasticity, but these factors did not influence the density, water absorption and thickness swelling.